2021
DOI: 10.1002/jctb.6952
|View full text |Cite
|
Sign up to set email alerts
|

Poly‐L‐lysine‐coated α‐lactalbumin nanoparticles: preparation, effect of pH, and stability under in vitro simulated gastrointestinal conditions

Abstract: BACKGROUND The development of bioactive compound delivery systems using protein‐based nanoparticles as carriers is a rapidly growing field of study. α‐Lactalbumin (α‐La) nanoparticles are adequate for this task because they are nonantigenic, biodegradable, and easily modifiable via the surface physical adsorption of other molecules. Here, the effect of poly‐L‐lysine (PLL) coating of α‐La nanoparticles on the stability against enzymatic degradation in the gastrointestinal tract was investigated. RESULTS α‐La na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(77 reference statements)
2
3
0
Order By: Relevance
“…It can be seen ( Figure 1 ) that the morphology of the α-LA nanoparticles, as observed by SEM, is basically spherical with particle sizes of approximately 150 nm. These sizes are consistent with the sizes determined by DLS in this study and by other authors [ 25 , 37 , 38 ] by TEM.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It can be seen ( Figure 1 ) that the morphology of the α-LA nanoparticles, as observed by SEM, is basically spherical with particle sizes of approximately 150 nm. These sizes are consistent with the sizes determined by DLS in this study and by other authors [ 25 , 37 , 38 ] by TEM.…”
Section: Resultssupporting
confidence: 93%
“…A minimal ζ potential of −30 mV is required for electrostatically stable nanoparticles and a minimal of −20 mV for steric stabilization [ 39 ]. Our data are consistent with the ζ potential values observed for other albumin nanoparticles [ 26 , 37 ]. These results indicate that, at the pH values used in the preparation (9 and 11) of the α-LA nanoparticles, electrostatic repulsion may play an important role in the Pickering stabilization of emulsions.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, Jiménez‐Cruz et al 24 . presented an outstanding work of Food Biotechnology in which a bioactive compound delivery system using protein‐based nanoparticles as carrier was developed.…”
mentioning
confidence: 99%
“…Finally, Jiménez-Cruz et al 24 presented an outstanding work of Food Biotechnology in which a bioactive compound delivery system using protein-based nanoparticles as carrier was developed. These authors showed that poly-L-lysine coating resulted in enhanced resistance of ⊍-lactalbumin nanoparticles to simulated gastrointestinal conditions.…”
mentioning
confidence: 99%